2007
DOI: 10.1109/tnsre.2007.897024
|View full text |Cite
|
Sign up to set email alerts
|

Performances Evaluation and Optimization of Brain Computer Interface Systems in a Copy Spelling Task

Abstract: The evaluation of the performances of brain-computer interface (BCI) systems could be difficult as a standard procedure does not exist. In fact, every research team creates its own experimental protocol (different input signals, different trial structure, different output devices, etc.) and this makes systems comparison difficult. Moreover, the great question is whether these experiments can be extrapolated to real world applications or not. To overcome some intrinsic limitations of the most used criteria a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 14 publications
0
45
0
Order By: Relevance
“…In this region one can select the classifiers to use (SWLDA and Support Vector Machine in the figure) and see their performances, according to the metric described in [11]. It is also possible to set some parameters relative to the various classifiers.…”
Section: The P3 Classifier Modulementioning
confidence: 99%
See 1 more Smart Citation
“…In this region one can select the classifiers to use (SWLDA and Support Vector Machine in the figure) and see their performances, according to the metric described in [11]. It is also possible to set some parameters relative to the various classifiers.…”
Section: The P3 Classifier Modulementioning
confidence: 99%
“…The accuracies of the classification are computed as well as the efficiency, by mean of the metric proposed in [11], where it has been demonstrated that this indicator is a reliable indicator of the performances of real BCI systems.…”
Section: Introductionmentioning
confidence: 99%
“…Control interface: it is the module responsible for the encoding as it deals with the translation of a LS or sequences Bianchi et al 2007a), in which the classification performances are stored and that must be updated as the experimental session goes on. Also, as the control interface knows the encoding strategies, it has to furnish to the other actors the maps for the translation of LSs into SSs.…”
Section: Main Actors Involved During a Trialmentioning
confidence: 99%
“…This approach was validated in healthy subjects [28] and potential end-users [29]. This system was also evaluated with regard to communication efficiency (as defined by Bianchi et al [30]), and the asynchronous system had greater efficiency in terms of communication speed and time to recover from errors compared with the synchronous version [31].…”
Section: Introductionmentioning
confidence: 99%